Proceedings of the ACM Internet Measurement Conference 2020
DOI: 10.1145/3419394.3423648
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Last-mile Congestion

Abstract: Last-mile is the centerpiece of broadband connectivity, as poor last-mile performance generally translates to poor quality of experience. In this work we investigate last-mile latency using traceroute data from RIPE Atlas probes located in 646 ASes and focus on recurrent performance degradation. We find that in normal times probes in only 10% ASes experience persistent last-mile congestion but we recorded 55% more congested ASes during the COVID-19 outbreak. Persistent last-mile congestion is not uncommon, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…RTT-based outage detection approaches, such as [1,4,6,15], have been proposed by utilizing different statistical models to characterize the RTT of all links to detect the network outages. Fontugne et al [1] first obtained the differential RTT of all links.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…RTT-based outage detection approaches, such as [1,4,6,15], have been proposed by utilizing different statistical models to characterize the RTT of all links to detect the network outages. Fontugne et al [1] first obtained the differential RTT of all links.…”
Section: Related Workmentioning
confidence: 99%
“…RTT-based outage detection approaches, such as [1,4,6,15], have been proposed by utilizing different statistical models to characterize the RTT of all links to detect the network outages. Fontugne et al [1] first obtained the differential RTT of all links. Then, they leveraged normal distribution to model the measurements and detected the network outages by applying the Wilson score.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Home Area Latency Measurement 2 aimed to provide a service that estimates the latency of a home network by calculating the difference between the RTT from a home node to a measurement server and the measurement server to the exit point of the home network. Fontugne et al revealed congestion and communication bottlenecks in the last mile by analyzing the traceroute data from RIPE Atlas in [8].…”
Section: Related Workmentioning
confidence: 99%